2006
DOI: 10.2164/jandrol.05121
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Seminal Parameters Associated With Environmental DDT Exposure andp,p′‐DDE Concentrations in Men in Chiapas, Mexico: A Cross‐Sectional Study

Abstract: ABSTRACT:In response to mounting concerns about the endocrine-disrupting influence of environmental chemicals on human health, this epidemiological study was initiated to test the hypothesis that nonoccupational exposure to the estrogenic pesticide 1,1,1-trichloro-2,2-bis(chlorodiphenyl)ethane (DDT) affects male reproductive parameters. One hundred and sixteen men aged 27 years (SD ϭ 8.2) living in malaria endemic-areas in Chiapas (Mexico), where DDT was sprayed until 2000, participated in a cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
3
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(103 citation statements)
references
References 35 publications
7
90
3
3
Order By: Relevance
“…Comprehensive literature is available for DDT due to the worldwide use of this compound as an insecticide. Serum levels of 10 M have been measured in subjects chronically exposed to DDT (Chen et al, 2005;De Jager et al, 2006). This being the case, it is predictable that any thyroid dysfunction following chronic exposure to DDT could be caused, at least in part, by a direct interaction of this insecticide with the TSHr (Brucker-Davis, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive literature is available for DDT due to the worldwide use of this compound as an insecticide. Serum levels of 10 M have been measured in subjects chronically exposed to DDT (Chen et al, 2005;De Jager et al, 2006). This being the case, it is predictable that any thyroid dysfunction following chronic exposure to DDT could be caused, at least in part, by a direct interaction of this insecticide with the TSHr (Brucker-Davis, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Now, 24 years later, it is disconcerting that the highest ΣDDT level in breast milk yet measured from South Africa (5.2 mg/l wm and 140 mg/kg mf; Table 1) was found in a breast milk sample collected about 60 km away from the previous highest ΣDDT. Despite numerous scientific assessments recommending that safe and sustainable alternatives to DDT should be urgently investigated and deployed (De Jager et al, 2006;De Jager et al, 2009;Eskenazi et al, 2009;Bornman et al, 2010;Bouwman et al, 2011), a relatively affluent African country is in a position to do much more to reduce exposures or to move away from DDT. It must be acknowledged however, that a previous attempt to switch from DDT to pyrethroids failed (Hargreaves et al, 2003;Maharaj et al, 2005), and that the expectations of proof of safety and sustainability of alternatives have probably increased due to that failure.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Several studies from the Limpopo Province in South Africa and studies from Mexico have consistently indicated impaired semen quality associated with environmental dichlorodiphenyl-ethylene (DDT)-exposure among people living in endemic malarias areas [43,44]. The question whether malarial fever could explain the results has unfortunately not been addressed.…”
Section: Occupational Hazardsmentioning
confidence: 99%